2015
DOI: 10.1021/acs.biochem.5b01014
|View full text |Cite
|
Sign up to set email alerts
|

YAP and TAZ Take Center Stage in Cancer

Abstract: The Hippo pathway was originally identified and named through screening for mutations in Drosophila, and the core components of the Hippo pathway are highly conserved in mammals. In the Hippo pathway, MST1/2 and LATS1/2 regulate downstream transcription coactivators YAP and TAZ, which mainly interact with TEAD family transcription factors to promote tissue proliferation, self-renewal of normal and cancer stem cells, migration, and carcinogenesis. The Hippo pathway was initially thought to be quite straightforw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 143 publications
0
79
0
Order By: Relevance
“…If yes, it would be important to check if other components of the Hippo signaling pathway are also involved in the formation of invadopodia. This could constitute another mechanism through which the Hippo signaling pathway impinges on cancer cell organization and metastasis [8] [9].…”
Section: Resultsmentioning
confidence: 99%
“…If yes, it would be important to check if other components of the Hippo signaling pathway are also involved in the formation of invadopodia. This could constitute another mechanism through which the Hippo signaling pathway impinges on cancer cell organization and metastasis [8] [9].…”
Section: Resultsmentioning
confidence: 99%
“…5 However, YAP and TAZ are the main culprits in cancer pathogenesis, mainly through their interaction with the TEAD family of transcription factors. 12 The exact mechanism of YAP in cancer development is still under investigation. Many previous studies have reported elevated YAP protein levels in various types of cancer, such as colorectal, gastric, and human hepatocellular carcinoma.…”
Section: Hippo Pathway and Cancermentioning
confidence: 99%
“…Many previous studies have reported elevated YAP protein levels in various types of cancer, such as colorectal, gastric, and human hepatocellular carcinoma. 12,13 In this context, YAP is often described as an oncogene and its increased expression in cancers correlates with poor prognosis. For example, increased YAP expression is associated with high clinical stage and short overall survival in colorectal and ovarian cancer.…”
Section: Hippo Pathway and Cancermentioning
confidence: 99%
“…Is activation of YAP/TAZ associated with endothelial apoptosis and enhanced lipid uptake in the vessel wall? What is the role of other known signalling pathways interacting with YAP/TAZ such as the Wnt pathway that was recently shown to be regulated by blood flow (12)(13)(14)? …”
Section: Editorialmentioning
confidence: 99%